Peningkatan Pengetahuan WUS Tentang Skrining Kanker Serviks Metode IVA Dengan Menggunakan Media Audiovisual - Dianna, Dianna; Fitriani, Henny; RCP, Riska (Institut Teknologi dan Bisnis Semarang, 2023)
The low number of IVA visits needs serious attention by optimizing activities in increasing IVA visits. Audiovisual media has the advantage that it can attract attention, provide a more real picture, and increase memory retention and is easy to remember. The purpose of this community service is: informing about cervical cancer screening using IVA method thoroughly through lectures, simulations / demonstrations, questions and answers, brainstorming and educational videos. The method of activity is carried out with stages of preparation, implementation, monitoring and evaluation. The results of the activity showed that counseling activities on cervical cancer screening IVA method using audiovisual media in RW 01 in Sungai Beliung sub-district had been well organized. Data analysis obtained the results of p value = 0.002 so that it can be concluded that there is a significant difference in knowledge between before and after getting education with video media.